Endodontic and Surgical Management of Iatrogenic Root Injury Caused by Orthodontic Miniscrew Placement: A Case Report - Saberi, Eshagh Ali; Farhad-Mollashahi, Narges; Havaei, Seyed Rohollah (Iranian Endodontic Journal, 2019)
One of the potential serious complications, associated with the inter-radicular placement of an orthodontic miniscrew, is root injury. This article reports the endodontic and surgical treatments of an iatrogenic root perforation in a mandibular first molar caused by the placement of an orthodontic miniscrew anchorage. The 24-month follow-up showed a successful treatment outcome. Keywords: Dental Root; Orthodontic Anchorage; Orthodontic Complications